Technical note: Towards a stronger observational support for haze pollution control by interpreting carbonaceous aerosol results derived from different measurement approaches - Y. Cheng; Y. Zhong; Z. Zhang; X. Cao; J. Liu (Atmospheric Chemistry and Physics)
As China's fine particulate matter (PM2.5) has decreased nationwide during the last decade, further improvement of air quality has become more challenging, imposing higher requirements on the observational support for the understanding of aerosol sources. This was particularly the case for the severe cold-climate region in Northeast China, which suffered from relatively slow decrease rate and high exposure risk of PM2.5. Here, we evaluated carbonaceous aerosol data measured by different sampling and analytical approaches based on field campaigns conducted during a frigid winter and an agricultural-fire-impacted spring in Harbin. For both the high- and low-volume sampling, a total of four sets of organic and elemental carbon results were derived by applying two commonly used temperature protocols (IMPROVE-A – i.e., IMPV – and NIOSH) to both untreated filters and those extracted by methanol. Only the IMPV-based results measured before the extraction were found to be indicative of aerosol sources, e.g., in reasonable accordance with secondary aerosol formation in winter and open-burning impacts in spring. Thus, the analytical method of IMPROVE-A with untreated samples is recommended for future field observations and source apportionments of PM2.5 in the studied region. In addition, although the low- and high-volume samplers typically led to comparable measurement results for various species, exceptions were identified for water-soluble potassium (K+) and some fire-emitted chromophores. We suggest that K+ and light absorption coefficients of brown carbon should be compared or integrated with caution across studies using different PM2.5 samplers.